The Health Promotion Strategy in Preventing Under The Red Line in Growth Toddlers at Kuta Baro District - Diza Fathamira Hamzah; Sri Rosita; Cut Juliana (Universitas Serambi Mekkah, 2023)
Under the red line is one illustration of malnutrition in toddlers. This can be prevented by strengthening health promotion as one of the prevention efforts. This study aims to determine the relationship between health promotion strategies and the prevention of under-fives under the red line. This type of research is descriptive -analytic with a survey design. The population in this study was 136 people with a sample of 58 mothers under five who were drawn using the accidental sampling method. Data collection was carried out using a questionnaire that had been designed by the researcher. Data analysis was performed univariately and bivariately using the chi-square test with 95% confidence intervals. The results showed that there was a significant relationship between advocacy (p value = 0.001), atmosphere building (p value = 0,03) and community empowerment (p value = 0.001) and prevention of under-fives under the red line. It is suggested to the Aceh Besar District Health Office to increase health promotion efforts in preventing under the red line by conducting training for cadres of service post integrated on a regular basis so that health promotion activities can be carried out optimally, besides that it is necessary to establish a under the red line budgeting policy for prevention of 10% of the village goverment funds. Keywords : Health Promotion, Nutritional Status, Public Health, Toddler, Malnutrition.